Implementasi Cloud Accounting System pada UMKM: Analisis Efisiensi dan Akurasi Laporan Keuangan - Putri, Diana (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
Abstract: This study aims to analyze the efficiency and accuracy of MSME financial statements after implementing a cloud accounting system. The research method is a qualitative case study, involving several MSMEs that have switched from manual or desktop accounting systems to a cloud-based system. Data were collected through in-depth interviews, observation, and financial statement document analysis. The results are expected to show a significant increase in the speed of financial statement preparation (efficiency) and a reduction in recording errors (accuracy). This study provides practical implications for MSME managers and policymakers to encourage technology adoption to improve financial governance.